THE EFFECT OF ENTREPRENEURSHIP-BASED CURRICULUM ON HIGHER EDUCATION INSTITUTION TOWARDS NON-ECONOMIC STUDENT’S ENTREPRENEURIAL INTEREST - Eddy Soeryanto Soegoto (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
ABSTRACTThe purpose of this research is to discover: (1) The influence of entrepreneurship-based curriculum of Higher Education Institutions (HEI) toward non-economic student’s entrepreneurial interest (2) the extent to which the influence of entrepreneurship-based curriculum of HEI affects non-economics student’s entrepreneurial interest. This research is a causality research with quantitative research method. Data collection was done by spreading questionnaires to 100 respondents attending the class of entrepreneurship course. The respondents are the students of non-economics department in Universitas Komputer Indonesia. Each statement on the questionnaire was rated with a Likert scale. Test of variability and reliability is done on the questionnaire data. Data analysis method using simple linear regression with IBM Statistical Social Science Program (SPSS) 20. The results showed that (1) the entrepreneurship-based curriculum of HEI has significant and positive influence on student’s entrepreneurial interest of non-economic department with a correlation coefficient of 0.987. The positive relationship indicates that the larger the portion of entrepreneurship education in the curriculum of HEI, the higher student’s entrepreneurship interest of non-economics department (2) the percentage of the entrepreneurial-based HEI curriculum influence of non-economic student’s entrepreneurial interest of is 97,4%.